2018
DOI: 10.3346/jkms.2018.33.e58
|View full text |Cite
|
Sign up to set email alerts
|

Cesium-137 Contaminated Roads and Health Problems in Residents: an Epidemiological Investigation in Seoul, 2011

Abstract: BackgroundIn 2011, two roads in a residential area in Seoul were found to be contaminated with the radionuclide cesium-137 (137Cs). In response to public concerns, an epidemiological study was conducted.MethodsThe standardized cancer incidence ratios in the affected and neighboring regions were calculated based on the central cancer registry. Households in the region were sampled using the random stratified sampling technique, and questionnaires were administered to family members, via home visit and via stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Poisson regression is commonly used in epidemiological research, as illustrated by Demoury et al [ 40 ], Armstrong-Hough et al [ 47 ], Niedzwiedz et al [ 48 ], Tang et al [ 49 ], and Teng et al [ 50 ], and Negative Binomial Regression fitted well in our models, accounting for the overdispersion issue, as also pointed out by Fairos et al [ 18 ], while the Stone’s test is rarely used. The more recent studies we have found on this topic mainly deal with a small number of risk sources, such as Masseret et al [ 39 ], Demoury et al [ 40 ], Ha et al [ 51 ], and Rodriguez-Villamizar et al [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poisson regression is commonly used in epidemiological research, as illustrated by Demoury et al [ 40 ], Armstrong-Hough et al [ 47 ], Niedzwiedz et al [ 48 ], Tang et al [ 49 ], and Teng et al [ 50 ], and Negative Binomial Regression fitted well in our models, accounting for the overdispersion issue, as also pointed out by Fairos et al [ 18 ], while the Stone’s test is rarely used. The more recent studies we have found on this topic mainly deal with a small number of risk sources, such as Masseret et al [ 39 ], Demoury et al [ 40 ], Ha et al [ 51 ], and Rodriguez-Villamizar et al [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…After five years of exposure to Cesium-137 at the Chernobyl accident, a discrete increase in cancer risk was observed 34 . A higher risk (18%) was observed for the development of solid neoplasms, between 1992 and 2009 [SIR: 1.18; 95%CI:1.15;1.22] 35 . The incidence of thyroid cancer increased in children and adolescents five years after the Chernobyl accident.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial effects after exposure to Cesium-137 were described subsequently to the Seul accident, where risk perception was higher in older women, with lower education levels, and in the most exposed individuals 35 . Therefore, risk communication must be further studied in victims of accidents with ionizing radiation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 137 Cs is the main nuclide in polluted soil, and it is a long-lived fission product that releases considerable heat (t 1/2 = 30.08 years, a β/γ emitter) and has a half-life of approximately 30 years in high-level radioactive liquid waste [6]. High levels of 137 Cs brought near the human body through inhalation or ingestion accumulate in tissue or muscles, which causes nausea, vomiting, diarrhea, bleeding, coma, or more severe scenarios leading to death [7].…”
Section: Introductionmentioning
confidence: 99%